Comparative Analysis of Water Infiltration Potential: A Study of Precast Permeable Blocks, Precast Impermeable Blocks, and Traditional Bricks - Bhusal, Gaurav; Koirala, Badal; Kharbuja, Sunita; Duwal, Rajan (Journal of Science and Engineering, 2024)
Groundwater depletion is a global issue leading to shrinking aquifers and sinking lands. The increase in the rate of usage of groundwater and the decrease in recharge rate is its main cause. Conversion of natural lands to concrete and bituminous roads, urbanization, and industrialization are blocking groundwater infiltration. In such an intricate scenario, the use of permeable blocks in the pavement could be a viable solution. With the use of permeable blocks in areas like low-traffic roads, parking lots and pedestrian walkways, the groundwater table will get recharged to some extent. Permeable blocks could be an eco-friendly paving material reducing surface runoff, ponding of water and flood risk too. This study has experimentally determined and compared the two major characteristics contributing to groundwater infiltration- porosity and infiltration rate of permeable blocks, impermeable blocks, and bricks used generally in pavement design. We found that permeable concrete blocks are 6.89 and 2.19 times more porous than impermeable concrete blocks and burnt clay bricks respectively. Moreover, the permeable concrete blocks infiltrate 816.96 and 171.89 times more water in an hour than impermeable concrete blocks and burnt clay bricks respectively through the center of the blocks and 320.96 and 38.26 times more water in an hour than impermeable concrete blocks and burnt clay bricks respectively at the joints.